Avaliação da resposta anti-inflamatória da Angiotensina 1-7 associada a lipossomas administrada por via inalatória em camundongos com encefalomielite autoimune experimental - Bárbara Fernandes Pinto (2018)
Multiple sclerosis (MS) is a chronic, progressive and autoimmune disease characterized by inflammatory infiltrates, gliosis, demyelination and neuroaxonal degeneration in the central nervous system. Although the disease is irreversible and progressive, several forms of treatment have been used to minimize the clinical effects of MS. However, many of these drugs used for MS treatment are expensive and have serious side effects, decreasing patients' adherence to treatment and in some cases being lethal. Therefore, it is relevant and necessary to evaluate new pathways and treatment therapeutic options strategies for treatment of multiple sclerosis. The objective of this study was to evaluate the neuroinflammatory response in mice with experimental autoimmune encephalomyelitis (EAE) nebulized with liposomes containing Angiotensin 1-7 [Ang-(1–7)] .The EAE model was induced in C57Bl/6 wildtype (WT) mice, aged 8-12 weeks, by subcutaneous administration of emulsion containing MOG 35-55, Mycobacterium tuberculosis and complete Freund's adjuvant (CFA). Animals of the Control (healthy) group, and EAE animals, were nebulized every 72 hours, either with saline, Ang-(1-7), or with empty liposomes, or with Ang-(1-7) containing encapsulated into liposomes, over 20 days. Body weight and clinical manifestations were evaluated. Regarding the inflammatory parameters, on the 20th day after induction the brain, spinal cord, lung and spleen vascular permeability of the brain, spinal cord, lung and spleen was evaluated, as well as and the concentration of interleukins IL-10, TNF-α, IL-1β and IL-6 in brain and spinal cord homogenyates tissue. In addition, the leukocyte-endothelium interaction in the spinal cord microvasculature was quantified by intravital microscopy, and spinal cord histopathological changes by H&E staining the spinal histopathological changes were quantified. The group treated with liposomes containing Ang-(1-7) presented lower clinical score, lower weight loss, reduced cerebral vascular, pulmonary permeability, and cerebral IL-6 concentration. By intravital microscopy, it was observed that there was an increase of the medullar leukocyte bearing rolling in the microvasculature medulla. In conclusion, for the first time showed that, animals with experimental autoimmune encephalomyelitis showed presented a improvement of clinical signs and inflammatory improvement response after the nebulization of liposomes containing Ang-(1-7). Altogehter, our results suggest a, thus demonstrating the important neuroprotective role of Ang-(1-7) when associated with liposomes and administered nasallyby inhalation.